Multi-millijoule few-cycle mid-infrared pulses through nonlinear self-compression in bulk - V. Shumakova (Nature Portfolio, 2016)
Exploring strong-field laser interaction requires pulses that are both energetic and short. Here, the authors demonstrate a mid-IR soliton-like pulse compression in a mm-long YAG crystal, reaching the multi-millijoule energy range and showing pulse filamentation in atmospheric air.